Effect of sun radiation exposure on indoor air quality of car interior in tropical country - Othoman, Mohamad Asyraf (2015)
Number of vehicle in Malaysia increasing rapidly and usually parked at open or un-shaded parking area due limited of roof parking facilities. Hot car interior after certain minutes or hours of parking due sun radiation exposure, forced car user to wait for a period of time to cool down the car interior temperature. Increase of car interior temperature caused heat stroke to living creature and degradation of material and finishes. The objective of this research are to determine air quality level in car interior due sun radiation exposure during a hot and sunny day in tropical country weather. The studies is focused to assess air quality parameters inside car interior such as temperature, particle matter (PM10), relative humidity and carbon dioxide. Parameter data for indoor air quality has been analyzed in five different modes. Each modes data collection has been repeated for three days to reduce uncertainty. From experimental results, in sun radiation exposure car interior temperature can exceed 60% from ambient temperature. Sunshade installation and lowered 20 mm all windows caused reduction of interior temperature between 3% to 7%. Heat developed inside enclosed vehicle effected scattering of particle matter PM10 in air. PM10 concentration increased when circulation of air from outside have by windows gap. Relative humidity decreased when car interior temperature increased. CO2 concentration is high at beginning of test but then gradually decrease to ambient concentration after certain period